The NpV and PuV Carbonate Systems: Thermodynamics and Coordination Chemistry. Issue 2 (8th January 2020) - Aupiais, Jean; Alexandre, Jean‐Charles; Sicre, Rémi; Siberchicot, Bruno; Topin, Sylvain; Moisy, Philippe; Dacheux, Nicolas
Abstract : New stability constants for Np V and Pu V carbonates have been established by coupling capillary electrophoresis (CE) and ICP‐MS at the ionic strength of 0.202 mol/kgwater in NaClO4 and at various temperatures. The thermodynamic data [variation of the molar enthalpy, Δr Hm ( T °) and entropy, Δr S m ( T ) of reaction] associated with the formation of the AnO2 CO3 – (An = Np, Pu), AnO2 (CO3 )2 3–, and AnO2 (CO4 )3 5– complexes were determined. A drastic decrease in molar entropy was observed between the second and third complexes, suggesting important structural changes. Ab initio molecular dynamics showed that the 1:3 complex is formed with two carbonate ligands located at a shorter distance and one at a longer distance, suggesting that the closer ligands are coordinated in a bidentate fashion to the plutonyl(V) moiety whereas the third ligand is monodentate. The variation of the electrophoretic mobilities as function of charge/size ratio confirms unambiguously that the triscarbonate complex of pentavalent plutonium structurally differs from that of hexavalent plutonium where all carbonates anions are bidentate. Abstract : The monodentate coordination mode of one carbonate in the triscarbonate complex of pentavalent plutonium has been evidenced by capillary electrophoresis and confirmed by quantum molecular dynamics and thermodynamics. This result confirms the capability of capillary electrophoresis to probe intramolecular distances.